Performance Measurement System in Islamic Bank: Some Issues and Considerations - Adib, Noval; Khalid, Siti Nabiha Abdul (Jurnal Akuntansi Multiparadigma, 2010)
There are various evidences show that business that complied with Islamic laws, i.e. Islamic business has succeeded. Islamic bank is the most prominent model of Islamic business that is acknowledged widely which could be proven by its existence in many countries, whether in Muslim majority countries or non-Muslim majority countries. As Islamic banks grow rapidly, an issue that needs to be addressed is regarding performance measurement in Islamic bank. However, even though there are many studies on Islamic banking, issues of performance measurement in Islamic bank receive very little attention among researchers. In fact, research on performance measurement in service sector is very rare compared to the manufacturing sector. The purpose of this article is to discuss issues on performance measurement in Islamic bank. As a banking system that based on Islamic tenets, Islamic bank is supposed to have certain unique criteria of performance. Some models of performance measurement commonly used in conventional banks will be analyzed to determine whether they are applicable in Islamic banks. Some issues will be discussed as well regarding the establishment of Islamic performance measurement model that can reflect comprehensive effectiveness that meets Islamic requirement of performance.